Individual inflammatory marker abnormalities or inflammatory marker scores to identify primary care patients with unexpected weight loss for cancer investigation? - Nicholson, BD; Oke, JL; Aveyard, P; Hamilton, WT; Hobbs, FDR (Springer Nature, 2021)
Background Combinations of inflammatory markers are used as prognostic scores in cancer patients with cachexia. We investigated whether they could also be used to prioritise patients attending primary care with unexpected weight loss for cancer investigation.